Tingkat Kebahagiaan dan Kesejahteraan Petani Cengkeh di Kecamatan Mandalawangi Kabupaten Pandeglang - Dahlia Anjani; Fitra Dilla Anggraeni; Ari Praja Rezaldi; Naf’an Tarihoran (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
This KKN activity is about the level of happiness and welfare of farmers in Mandalawangi District, Pandeglang Regency.. This research is motivated by the low income of clove farmers during the rainy season which results in reduced welfare. Through research, there are several factors that reduce farmers' income, including infrastructure and cost factors. The aim of this research is to find out how influential clove income is on the welfare of farmers. The research method used is quantitative with the data source being the results of interviews. The research results show that there are several suggestions for farmers to handle clove management when the rainy season arrives. This research will hopefully have a positive impact on the level of happiness and welfare of clove farmers in Mandalawangi District, Pandeglang Regency.